Pengekang Crossties di Zona Tekan Balok dengan Pembebanan Siklik - Priastiwi, Yulita Arni; Imran, Iswandi; Nuroji, Nuroji; Hidayat, Arif (Department of Civil Engineering, Diponegoro University, 2018)
Crossties that was installed as a confinement in the compression zone of the beam is proven can increase the ductility, especially when receiving the earthquake load. Using an experimental study, this paper explains the effect of crossties which was installed in compression zone of the beam. The model was a simplification of the plastic hinge of the beam. The beam was enlarged in the center of the span and would be loaded with a cyclic of point load, so as to produced the largest moment and shear fields in the face beam of the column. Moreover, the loading was provided by the displacement control system to achieve the ultimate condition. The results show that the crossties significantly increases the displacement and curvature ductility of the beams of 58.7% and 78.2%, respectively, compared to the beam without confinement. In addition, the load cycle formed by cyclic loading increases to 43 cycles in beam with crossties, meanwhile the beam without confinement can only survive up to 33 cycles. The crossties could also increase the cumulative value of inelastic displacement that occurs up to 98%, whereas its energy dissipation value is six times than the beam without confinement. On the other hand, the maximum load and capacity moment only increase about 6.5%.